Research on 5G lite approaches and implementation strategies - QIU Jianshu; ZHU Ziyuan; SHI Yu (Dianxin kexue)
5G lite is achieved by appropriately reducing performance metrics to trade off for lower terminal costs and power consumption, thereby meeting the needs of application scenarios such as the IoT. In conjunction with the 3GPP’s RedCap technology specifications, 5G light-weighting methods, their benefits, and impacts on the network was presented. A comparative analysis of two implementation approaches was also conducted: terminal and network coordinated reduction, and terminal self-reduction. Based on this analysis, a converged 5G lite terminal implementation scheme was proposed, enabling terminal products to better adapt to varied 5G lite deployment strategies of different operators.